The Effect APE Maze On Fine Motor Children 4-6 Years Old In Kartini Kindergarten Curah Buntu Jember : Effect APE Maze On Fine Motor Children 4-6 Years Old In Kartini Kindergarten Curah Buntu Jember - Putri Cindy Laura Faradila; Yuningsih (Fetus : Journal of Midwifery, 2025)
Fine motor development children aged 0–6 years progresses rapidly. According to Ministry of Health (2020), 18% of Indonesian children experience fine motor disorders. This condition often leads to difficulties in concentration, low self-confidence, and a tendency to become dependent. An activity proven to support fine motor development is the use of a Maze Educational Play Tool (APE Maze). The pupose to analyze APE Maze effects on the fine motor development of children aged 4–6 years at Kartini Kindergarten, Curah Buntu Village, Jember. This study applied a pre-post test control group experimental. Sampling was conducted using a simple random technique. Out of 25 children, 24 were selected and divided into three groups: APE Maze Level 1, level 2, and a control group. Data were collected using the Denver Developmental Screening Test II (DDST II). The Kolmogorov–Smirnov test was used for normality, while the Wilcoxon and Mann–Whitney U tests were used bivariate analysis. Results the Kolmogorov–Smirnov test showed < 0,001, indicating non-normal data distribution. APE Maze Level 1 had a significant effect on fine motor skills of children aged 4-6 years with p value 0,008< a 0,05. As did APE Maze Level 2 with Asymp. Sig. (2-tailed) p value 0,01< a 0,05. The conclusion is APE Maze significantly influences fine motor development in children aged 4–6 years. Children with optimal fine motor skills are more likely to become independent and high-achieving individuals. Thus, APE Maze can be considered an effective strategy to enhance early childhood motor development.